2015 23rd European Signal Processing Conference (EUSIPCO) 2015
DOI: 10.1109/eusipco.2015.7362459
|View full text |Cite
|
Sign up to set email alerts
|

Post-reconstruction deconvolution of PET images by total generalized variation regularization

Abstract: Improving the quality of positron emission tomography (PET) images, affected by low resolution and high level of noise, is a challenging task in nuclear medicine and radiotherapy. This work proposes a restoration method, achieved after tomographic reconstruction of the images and targeting clinical situations where raw data are often not accessible. Based on inverse problem methods, our contribution introduces the recently developed total generalized variation (TGV) norm to regularize PET image deconvolution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Several researchers have shown that the DP can be used to guide penalty weight selection. In particular, Guerit et al have shown via KL‐divergence that a penalty sub‐update can be added to Poisson denoising algorithms. However, this method relies on the Poisson discrepancy metric for image quality, which may not be optimal in the MMSE sense, and its extension to a two parameter model is unclear.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers have shown that the DP can be used to guide penalty weight selection. In particular, Guerit et al have shown via KL‐divergence that a penalty sub‐update can be added to Poisson denoising algorithms. However, this method relies on the Poisson discrepancy metric for image quality, which may not be optimal in the MMSE sense, and its extension to a two parameter model is unclear.…”
Section: Methodsmentioning
confidence: 99%
“…At present, several researchers have developed theoretical frameworks based on the discrepancy principle (DP) given Gaussian and Poisson noise for estimating the penalty weights of single parameters. [28][29][30][31] The DP is the idea that the uncertainty of the data should match the variability of the object or penalty function. However, it has been pointed out by several researchers that this match does not necessarily result in a minimum mean squared error (MMSE) image, 32,33 nor if MMSE is necessarily the right goal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the synthetic USAF transmission target is piecewise constant, we select the TV-norm for g 1 in Eqs. (30) and (37).…”
Section: Simulationsmentioning
confidence: 99%
“…This setting is of interest whenever one has no direct access to the sinogram of the acquisition. We also note that a second-order deconvolution approach, based on total generalized variation [8] has been proposed for static PET images in [9].…”
Section: Related Workmentioning
confidence: 99%